2019
DOI: 10.3899/jrheum.180549
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated Regulation of Mucin-type O-glycosylation Pathway: A Putative Mechanism of Salivary Gland Dysfunction in Sjögren Syndrome

Abstract: Objective.To investigate microRNA (miRNA) that is potentially implicated in primary Sjögren syndrome (pSS)–related salivary hypofunction in labial salivary glands and to study miRNA-mediated mechanisms underlying oral dryness and altered rheology, focusing on the mucin O-glycosylation pathway.Methods.We performed miRNA expression profiling in minor salivary gland samples of patients with pSS presenting a different impairment in their unstimulated salivary flow rate. A computational in silico analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…Conversely, shared downregulated genes showed enrichment in processes associated with O-glycan processing, ER to Golgi vesicle-mediated transport, carbohydrate metabolic process, and protein N-linked glycosylation via asparagine ( Supplementary Figure S5 and Supplementary Table S8 ). Interestingly, the observed downregulation of genes important for normal glycan function is in good agreement with the suggested role glycans play in influencing salivary flow, which is commonly reduced in pSS patients ( 68 ).…”
Section: Resultssupporting
confidence: 83%
“…Conversely, shared downregulated genes showed enrichment in processes associated with O-glycan processing, ER to Golgi vesicle-mediated transport, carbohydrate metabolic process, and protein N-linked glycosylation via asparagine ( Supplementary Figure S5 and Supplementary Table S8 ). Interestingly, the observed downregulation of genes important for normal glycan function is in good agreement with the suggested role glycans play in influencing salivary flow, which is commonly reduced in pSS patients ( 68 ).…”
Section: Resultssupporting
confidence: 83%
“…In LSG from SS-patients with LFS compared to sicca controls, we found 3 miRNAs differentially expressed (hsa-miR-769-5p, hsa-miR-493-5p and hsa-miR-181d-5p), implicated in regulating 4 genes encoding for glycosyltransferases of the Golgi apparatus involved in mucin O-Glycan biosynthesis (POC1B-GALNT4, GALNT4, GALNT10 and C1GALT1) (Supplementary Table S3). This observation (Table 2) is in agreement with a previous report connecting this miRNA to the downregulation of GALNT4 ( 61), a member of the GalNAc-T family of enzymes which initiates Oglycosylation of mucins in epithelial cells, a process that is altered in SS-patients (23,61). The downregulation on hsa-miR-769-5p observed in LSG from SS-patients with HFS compared to SSpatients with LFS (Table 2) may be a consequence of the loss of the epithelial component and its replacement by inflammatory cells in the LSG from SS-patients with HFS.…”
Section: Functional Enrichment Analysis Of Differentially Expressed M...supporting
confidence: 92%
“…Functional annotation of the differently expressed miRNAs showed that the miRNAs target and regulate proteins that are involved in salivary secretion and various immune system processes (Table 2), which is reflected in significantly lower UWS and SWS flow rates and more extensive focal lymphocytic infiltration in the pSS group. Dysregulation of some of these pathways, for example, TGF‐β and Mucin‐type O glycosylation, has previously been described in relation to pSS 13,31 . However, interpretation of signaling pathways identified in silico should be done with caution, as some miRNAs are more frequently studied and reported and few signaling pathways have been verified in human oral tissues.…”
Section: Discussionmentioning
confidence: 99%